1998
DOI: 10.1002/art.1790110206
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and physical abuse in women with fibromyalgia: Association with outpatient health care utilization and pain medication usage

Abstract: Objective. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 60 publications
3
87
1
9
Order By: Relevance
“…Most authors describe a higher trauma prevalence in patients with FM compared with patients with other chronic pain conditions, although this finding is not universal (11)(12)(13)(14)(15). Childhood sexual and lifetime sexual and physical abuse as well as lifetime emotional abuse and neglect have been shown to be more prevalent in FM patients (12)(13)(14)16). However, a relationship between trauma history and symptom severity may exist (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors describe a higher trauma prevalence in patients with FM compared with patients with other chronic pain conditions, although this finding is not universal (11)(12)(13)(14)(15). Childhood sexual and lifetime sexual and physical abuse as well as lifetime emotional abuse and neglect have been shown to be more prevalent in FM patients (12)(13)(14)16). However, a relationship between trauma history and symptom severity may exist (17).…”
Section: Introductionmentioning
confidence: 99%
“…However, a relationship between trauma history and symptom severity may exist (17). Studies suggest that patients reporting childhood abuse experience greater psychological distress; have more severe physical symptoms, greater functional disability, and poorer psychological adjustment; and utilize more health care services (15)(16)(17)(18). The high level of stress during and after a trauma may give rise to incomplete or maladaptive processing of the event, which may result in the information-processing deficit known as "dissociation," which is understood as a "disruption of the usually integrated functions of consciousness, memory, identity, or perceptions of the environment" (19).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual abuse, violence, the threat or the witnessing of either, which have been mentioned in some of our respondents have also been described as causes of psychological trauma. Other authors found a high prevalence (> 30%) of sexual and physical abuse in women with FM and reported higher rates of abuse in these patients as compared with a group of women without FM [45][46][47]. However, still other authors questioned the association between sexual abuse and FM onset [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that antecedent traumatic psychological experiences may play an etiologic role in the persistence of symptoms after the infection has been adequately treated (20). This relationship has been demonstrated in other MUS conditions, including multiple chemical sensitivity (21), chronic fatigue syndrome, (22), irritable bowel syndrome (23)(24)(25)(26), chronic pelvic pain (27), and fibromyalgia (28)(29)(30).…”
Section: Lyme Disease Medically Unexplained Syndromes and The Anxiomentioning
confidence: 96%